2009
DOI: 10.1021/ja9070927
|View full text |Cite
|
Sign up to set email alerts
|

Nonpolymeric Thermosensitive Supramolecules

Abstract: Here we show 2'-deoxyguanosine derivatives that self-assemble in aqueous media into discrete supramolecular hexadecamers and exhibit the lower critical solution temperature (LCST) phenomenon. Spectroscopic, calorimetric and electron microscopy studies support the fact that above transition temperature (T t ) the supramolecules further assemble into nanoscopic spherical globules of low polydispersity. Furthermore, the T t can be tuned to higher values by the addition of a more hydrophilic derivative. These find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 29 publications
4
61
0
Order By: Relevance
“…Specifically, the thermodynamic stability, molecularity and fidelity of such supramolecules is influenced by parameters such as: (a) the nature and the position of the functional group at the 8-phenyl ring,14, 15 and (b) the nature and the size of the moieties attached to the 3'- and 5'-OH groups of the furanose ring 16,17. The medium, or extrinsic parameters, also influences the assembly process 18,19. For example, in organic media, and under identical conditions, the meta -acetylphenyl derivative ( mAGi ) assembles into a hexadecamer, while its para acetylphenyl isomer ( pAGi ) assembles into an octamer (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the thermodynamic stability, molecularity and fidelity of such supramolecules is influenced by parameters such as: (a) the nature and the position of the functional group at the 8-phenyl ring,14, 15 and (b) the nature and the size of the moieties attached to the 3'- and 5'-OH groups of the furanose ring 16,17. The medium, or extrinsic parameters, also influences the assembly process 18,19. For example, in organic media, and under identical conditions, the meta -acetylphenyl derivative ( mAGi ) assembles into a hexadecamer, while its para acetylphenyl isomer ( pAGi ) assembles into an octamer (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, they demonstrated that the molecule is able to self-assemble in water as a result of the formation of a hexadecamer. [6] They attributed the enhanced stability to a combination of factors, including the formation of extra H bonds and increased p-stacking interactions. Nevertheless, the studies were performed by using 1 m KCl, which emphasizes the difficulties of creating hydrogen bonds between small molecules in water.…”
mentioning
confidence: 99%
“…Experimentally, however, we have only identified one type of dodecamer in solution. 18, 2122, 37, 3940 Such experimental evidence also strongly suggests that the observed 3 T-SGQ results from the stacking of a third tetrad on a pre-existing D 4 -symmetric 2 T-SGQ. Therefore, we can deduce that the dodecamer formed must have at least one homomeric interface ( hh or tt ), which were the ones selected for further MDS studies (Scheme 1).…”
Section: Resultsmentioning
confidence: 78%
“…While we anticipate these results to be broadly general to a wide variety of SGQs made from 8ArGs, there are several outstanding questions pertaining to derivatives lacking the meta-acetylphenyl moiety. For example, we reported the propensity of a 8-(3-pyridyl)-G derivative to form dodecameric SGQs (3T–SGQs) with high fidelity, 18, 2122, 37, 3940 because attractive dipole-dipole interactions were enough to stabilize the supramolecular state up to that molecularity, yet, not enough to sustain a stable 4T–SGQ. But, what about other moieties and functionalities?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation